Reduction of Salivary Streptococcus mutans Colonies in Children After Rinsing with 2.5% Green Tea Solution - Fajriani, Fajriani; Andriani, Jennifer N. (Journal of Dentistry Indonesia, 2014)
Dental caries is a problematic area in pediatric dentistry, with Streptococcus mutans as the dominant bacterial cause. Green tea solution and chlorhexidine were effective in reducing the number of Streptococcus mutans. But study about the differences of these two materials has not been done. Objective: The aim of this study was to determine differences in the effectiveness of rinsing with 0.2% chlorhexidine and 2.5% green tea solution in reducing the number of Streptococcus mutans. Methods: This study is quase experimental study with cross-over design. Thirty children aged 6-12 years with poor OHI-S index were participated. Samples of saliva were taken respectively before rinsing for 3 seconds with 0.2% chlorhexidine solution and a solution of 2.5% green tea and 15 minutes followed 30 minutes after rinsing intervention. Saliva samples were taken to the laboratory then the number of Streptococcus mutans count were evaluated. The statistical analysis were performed by SPSS version 18.0 with ANOVA, t-paired and LSD test. Results: ANOVA test result showed that the decrease generated by each mouthwash is a significant reduction. T-paired test result showed that there is no difference in the number of Streptococcus mutans colonies significantly between chlorhexidine and green tea solution at 15 minutes dan 30 minutes after rinsing. Conclusion: There is no significant difference between chlorhexidine and green tea solution in reducing the number of Streptococcus mutans.